PARTISIPASI ANGGOTA KELOMPOK “MASTALI MADU” DALAM KONSERVASI MANGROVE DI KELURAHAN PURNAMA KECAMATAN DUMAI BARAT - Aisyah Putri; Firman Nugroho; Ridar Hendri (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2026)
The destruction of the mangrove ecosystem in Purnama Village is a cause for concern among the community, especially in Purnama Village. Efforts to preserve mangroves with community involvement are needed. The active participation of group members such as the ‘Mastali Madu’ group is very important in the implementation of mangrove conservation activities. This study aims to analyse the forms of participation, supporting and inhibiting factors, and the impacts felt by members of ‘Mastali Madu’ when involved in mangrove conservation. This study was conducted in Purnama Village, using qualitative methods with a phenomenological approach, which involved observation, in-depth interviews, and documentation. The results of the study show that the forms of participation of Mastali Madu group members in mangrove conservation are classified as active, especially in expressing opinions and carrying out activities. The supporting factors for participation are the availability of opportunities, willingness, and ability. The inhibiting factors include economic factors and a lack of training and support. The impact of member participation is positive, such as increased knowledge and awareness of mangrove conservation, but there are also negative impacts in the form of increased workload and social conflicts